The Relationship of Stress Levels to Noise Exposure - Angeline Novia Toemon; Anna Marthea Veronicha (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the relationship between stress levels and noise exposure among furniture workers. This study is an analytical descriptive research with a cross-sectional study design approach. The research location is at a furniture workshop in the Pahandut Seberang area of Palangka Raya. The study population consists of all workers in the furniture workshop in Pahandut Seberang and residents within a 100-meter radius of the workshop, who are considered to be at risk of noise exposure. The sample for this study was taken using a random sampling method. Data analysis was conducted using the Chi-square test, with a confidence level of 95% (p = 0.05), and the results are considered significant if p ≤ 0.05. The results showed p < 0.05, with a p-value of 0.004, indicating that there is a significant relationship between noise exposure and stress levels among workers and residents in the furniture workshop area of Pahandut Seberang. This result suggests that exposure to noise above 85 dBA may have a significant impact on stress levels in this population.